ANALISA AKUNTANSI PEMBIAYAAN DENGAN PRINSIP BAGI HASIL DAN JUAL BELI DI PERBANKAN SYARIAH - Indria Widyastuti (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
Banking functions are as mediation institutions in finance or liaison between the parties that the excess funds (surplus funds) with those who loss of funds(deficit fund) because bank collects funds fromthe public (finance) and provide funding (financial) to those in need. Islamic banks collected funds distributed based onthe patterns of distribution of funds is justified in Islamic principles. Financing based on Sharia Principles is to provide cash to who loss of funds and must to return the money after a certain period of time in exchange or for the results. Financing on business activities or other activities stated in accordance with Sharia financing among other things based on the principle of profit sharing, which profit sharing principle is accompanied by equity, the principle of sale and purchase and capital goods financing with the principle of the lease without selection or by selection of the transfer of ownership of goods hired. Islamic banksfund distributioncan be done throughthe followingthreepatterns: the principle ofsale and purchase financingwhich includesfinancing with principles Murabaha, Salam, IstishnaandIjarah. The next principle is lossingprofitsharefinancingprinciplescoveringof Mudaraba financingandMusharaka financing. The otherfinancingprinciplescoveringHawalah, RahnandQardh. In this study analyzed the principle used in financing by Islamic. Transaction financing in the form of profit sharing are Mudaraba and Musharaka. Transaction financing in the form of sale & purchase are Murabaha, Salam and Istishna. Financing in the form of leasing is Ijarah Keywords : financing, profit sharing, Islamic banks.